The Master Architects : Building the United States Foreign Service 1890-1913 - Werking, Richard Hume (Book collections on Project MUSE., 1977)
During the twenty years before World War I, several key figures worked to improve the foreign service and to reform its appointment system. Richard Hume Werking explores both the methods and the motives of these ""master architects."" Unlike other scholars, Werking finds that the foundations and general structure of the United States foreign service emerged before World War I. He sees its development as prompted less by foreign crises than by economic conditions -- particularly the need to stimulate export trade. Indispensable to its growth were the dedicated efforts of bureaucrats who were lo.